Edukasi Bahaya Merokok sebagai Upaya Peningkatan Pengetahuan dan Kesadaran Masyarakat di Desa Tanjung Beringin Dusun III - Fiya Diniarti; Aldo Wijaya; Anes Adesti; Ismi Trirahayu; Irmiyani Irmiyani; Juli Mardani; Leni Anugrah (Jurnal Pengabdian Mitra Persada, 2026)
Smoking is a high-risk behavior that has a significant impact on public health, affecting both active and passive smokers. The high prevalence of smoking in the community indicates a low level of knowledge and awareness regarding the dangers of smoking. This community service activity aimed to improve public knowledge and awareness of the health risks associated with smoking through health education. A descriptive method with a participatory approach was applied through face-to-face counseling sessions. The activity was conducted in Tanjung Beringin Village, Hamlet III, from November 24 to December 22, 2025, involving 58 participants consisting of adolescents and adults. Program evaluation was carried out using pre-test and post-test questionnaires. The results showed an increase in participants’ knowledge after the counseling sessions, particularly regarding harmful substances in cigarettes and their effects on health. In addition, participants demonstrated positive attitude changes, including increased awareness to reduce smoking behavior and to create smoke-free environments. These findings indicate that health education is effective as a promotive and preventive effort to improve public health status. Therefore, smoking hazard education should be implemented continuously and integrated with other community health programs